Curriculum Effects On University Students’ English Language Achievement - Cardenas Moyano Maria Yadira; Campana Dias Diana Carolina; Campana Dias Diana Carolina; Guadalupe Bravo Luis Oswaldo; Guadalupe Bravo Luis Oswaldo; Bravo Montenegro Marco Antonio; Bravo Montenegro Marco Antonio (European Scientific Journal, ESJ, 2018)
The objective of this research is to identify, analyze and determine the curricular effects in the linguistic achievement to implement a curricular redesign and improve the English language teaching-learning to students and teachers of the Escuela Superior Politécnica of Chimborazo Language Center. The research used the communicative method, using several comprehensive techniques based on language skills: listening, speaking, reading and writing. It was considered the critical-proactive paradigm to look for solutions in an environment of description and understanding of the educational, social and cultural process. Surveys were applied to measure the learning achievement of the language, as an independent variable, applied to one hundred and fifty students and the curricular effect as a dependent variable directed to fifty five teachers of the Language Center, as well as, interviews to four directors of the Language Center. At the level of the students, it was concluded that the level of English is still basic, therefore, a new instrument is needed that proposes: methodology, techniques and updated contents to reach a competitive level. Most teachers indicate that the curriculum established by the Center must be updated in order to make better teaching possible.